(untitled) (Journal of Global Accounting, 2025)
This study examined the impact of environmental cost on financial performance of listed downstream oil and gas companies in Nigeria. Correlational research design was employed for the study. Data were extracted from the financial statements of six listed downstream oil and gas companies in Nigeria for a period of ten years (2014-2023). The hypotheses formulated for the study was tested using multiple regressions analysis. The study shows that waste community development cost has significant impact on financial performance while waste management costs and employee health and safety costs have insignificant impact on financial performance of listed downstream oil and gas companies in Nigeria. The study concludes that community development cost is one environmental accounting determinant that influences financial performance of the companies under study. Therefore, the study recommended that the management should incorporate community development initiatives into their overall business strategy, recognizing that investing in local communities can enhance brand reputation as well as customer loyalty, ultimately leading to improved financial performance. More so, there is need to allocate more resources towards renewable energy projects to reduce reliance on fossil fuels, mitigate environmental impact, and enhance long-term financial sustainability.